Preparing for smart voice assistants: Cultural histories and media innovations. (July 2021) - Humphry, Justine; Chesher, Chris
Smart voice assistants have become popular thanks largely to their default naturalistic female voices and helpful personae. In this article, we trace changes in robot voices in popular culture and explain how this history influenced the voice design of smart voice assistants. Our research draws on cultural analysis of Hollywood and international films, television and literature, and observations from our personal experiences with voice assistants. We argue that designers of devices like the Google Home and Amazon Echo inherited a cultural imaginary of alien and dangerous robots with artificial voices and personalities. Manufacturers leveraged techniques of modality, personae and invocation and pre-existing social connotations of the voice to create positive associations of these devices in the home. We conclude by arguing that smart voice assistants are new media innovations prepared for consumers through pre-domestication and represent an emerging regime of power and influence based on technologised voice interaction.